TRANSLATING IDIOMS OF ENGLISH ROAD SIGN TERMS INTO UZBEK - Xoshbaqova Nasiba Nurqobil qizi (Western European Studies, 2025)
This study explores the translation of English road sign-related idioms into Uzbek, focusing on the cultural and linguistic nuances that arise in the process. Idioms derived from road signs and travel terms are common in both languages and often carry deeper meanings related to decision-making, progress, and life's challenges. By comparing ten specific idioms, including "Cross the bridge when you come to it," "At a crossroads," and "Hit the road," the study investigates how these expressions are conceptualized in both languages. Through direct translations and cultural analysis, the study reveals both similarities and subtle differences in the way these idioms are used, emphasizing how road metaphors reflect cultural perspectives on movement and change. The findings demonstrate that while the core meanings of the idioms are often preserved, differences in linguistic structure and cultural context can affect their interpretation. This research contributes to the understanding of how metaphorical language, especially related to roads and journeys, shapes communication and thought patterns across languages
Keywords: road signs; translation; cultural context